Effect of Hydrogen Peroxide on the Antibacterial Substantivity of Chlorhexidine - Shahriar Shahriari; Zahed Mohammadi; Mohammadi Mehdi Mokhtari; Rasoul Yousefi (Hindawi Limited, 2010)
The purpose of this in vitro study was to assess the effect of hydrogen peroxide on the antibacterial substantivity of chlorhexidine (CHX). Seventy-five dentine tubes prepared from human maxillary central and lateral incisor teeth were used. After contamination with Enterococcus faecalis for 14 days, the specimens were divided into five groups as follows: CHX, H2O2, CHX + H2O2, infected dentine tubes (positive control), and sterile dentine tubes (negative control). Dentine chips were collected with round burs into tryptic soy broth, and after culturing, the number of colony-forming units (CFU) was counted. The number of CFU was minimum in the first cultures in all experimental groups, and the results obtained were significantly different from each other at any time period (𝑃<.05). At the first culture, the number of CFU in the CHX + H2O2 group was lower than other two groups. At the other experimental periods, the CHX group showed the most effective antibacterial action (𝑃<.05). Hydrogen peroxide group showed the worst result at all periods. In each group, the number of CFU increased significantly by time lapse (𝑃<.05). In conclusion, H2O2 had no additive effect on the residual antibacterial activity of CHX.